Informal incentives and labor markets - Matthias Fahn; Takeshi Murooka (Johannes Kepler University of Linz, Department of Economics, 2022)
This paper theoretically investigates how labor-market tightness affects market outcomes if firms use informal and self-enforcing agreements to motivate workers. We characterize profit-maximizing equilibria and derive the following results. First, an increase in the supply of homogenous workers can increase wages. Second, even though all workers are identical in terms of skills or productivity, a discrimination equilibrium exists in which a group of majority workers are paid higher wages than a group of minority workers. Third, minimum wages can reduce such discrimination and increase employment. We discuss how these results are consistent with empirical evidence on immigration and a gender pay gap, and provide new testable implications.
Keywords: D21; D86; J21; J38; J61; J71; 330; Informal Incentives; Labor Supply; Immigration; Wage Discrimination; Minimum Wage